Use of monoclonal antibodies in an ELISA to detect IgM class antibodies specific for Toxoplasma gondii. Issue 8 (August 1987) - Balfour, A H; Harford, J P; Goodall, M
Abstract : Two monoclonal antibodies CH6 and C1E3 were used in an antibody class capture assay for the detection of IgM antibodies specific for Toxoplasma gondii. CH6 was used on the solid phase to capture human IgM. After a Toxoplasma gondii antigen had been added, specifically bound material was detected using C1E3 coupled to horseradish peroxidase. The assay was compared with an established system using polyclonal antisera at both the capture and antigen detection stages. A good correlation was found, with 97.3% (125 of 128) of sera giving the same classification in both assays. Three sera were positive only in the polyclonal system. No false positive results were found when 118 negative sera were examined. The two monoclonal antibodies provide a viable alternative to the use of polyclonal sera at the capture and antigen detection stages in the antibody class capture assay for the measurement of specific IgM against T gondii.